ANALISIS PENGARUH ZAKAT DAN INVESTASI TERHADAP PENDAPATAN PER KAPITA 2020-2021 - Muhtadin Widyoko (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Income per capita is the average annual income of the community. Community welfare can be viewed through the per capita income of the community in a certain area. From a macroeconomic point of view, investment is able to drive growth rather than people's per capita income. This is done by adding gross fixed capital in a region until it reaches the stage of full employment. In addition to investment, zakat from an Islamic economic perspective is also felt to be able to increase people's welfare. Zakat is a socio-economic instrument that creates prosperity through an equal distribution process. Central Java as one of the provinces on the island of Java has the lowest per capita income on the island of Java. This research was conducted to review the effect of investment and zakat in Central Java on income per capita. Through a time series research process that takes 2020-2021 and also a cross section with a sample of 32 cities and regencies, the aim is to review the effect of zakat and investment on each region in Central Java. Apart from the zakat variable through the micro dimension of NZI and the macro dimension of NZI and investment, this research uses a control variable in the form of government social assistance (Bansos) originating from the APBD of each region in Central Java. The results of this study indicate that simultaneously the investment variable, zakat which is divided into the micro dimension NZI and the macro dimension NZI, and also the control variable in the form of social assistance has a significant influence on income per capita in Central Java in 2020-2021. From this, investment and zakat are considered quite effective in increasing the per capita income of the people of Central Java. Keywords: IZN Micro Dimensions, IZN Macro Dimensions, Investment, Social Funding.